102 - IPA Guidelines on Dementia and Agitation: From Provisional to Final. (October 2021) - Cummings, Jeffrey; Sano, Mary; Mintzer, Jacobo; Rosenberg, Paul; Splaine, Michael
Abstract : Agitation is common across neuropsychiatric disorders and contributes to disability, institutionalization, and diminished quality of life for patients and their caregivers. In 2015 IPA convened a transparent process to build a consensus definition of agitation and agreement on what elements should be included in the syndrome that resulted in publication of provisional guidelines. (Cummings et al, 2015) In the 2020-2021 year, the two co-chairs of this symposium have led a new workgroup to make the provisional consensus definition of agitation in patients with cognitive disorders that can be applied in epidemiologic, non-interventional clinical, pharmacologic, non-pharmacologic interventional, and neurobiological studies and guide treatment final. Co-Chairs will discuss methods used in updating and findings and compare changes made to the provisional guidelines. Dr. Sano will present new findings on the biological basis of agitation in dementia and Dr. Mintzer will present on application of guidelines in the special circumstances of persons in palliative and hospice care. Dr. Rosenberg will discuss the special circumstance of agitation care in hospital emergency departments. Mr. Splaine will present findings about the utilization of the 2015 guidelines in the peer reviewed literature, professional and government dementia care guidance, and clinical trials. Cummings, J., Mintzer, J., Brodaty, H., Sano, M., Banerjee, S., Devanand, D., … Zhong, K. (2015). Agitation in cognitive disorders: International Psychogeriatric Association provisional consensus clinical and research definition. International Psychogeriatrics, 27(1), 7-17. doi:10.1017/S1041610214001963